2015
DOI: 10.1371/journal.pone.0120023
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Mercapturic Acids of Acrolein and Crotonaldehyde in the Urine of Chinese Women in Singapore Who Regularly Cook at Home

Abstract: Lung cancer is unusually common among non-smoking women in Southeastern Asia but the causes of this frequently fatal disease are not well understood. Several epidemiology studies indicate that inhalation of fumes from high temperature Chinese style cooking with a wok may be a cause. Only one previous study investigated uptake of potential toxicants and carcinogens by women who cook with a wok. We enrolled three-hundred twenty-eight non-smoking women from Singapore for this study. Each provided a spot urine sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…We also examined other published data regarding urinary concentrations of SPMA in subjects without occupational exposure, all analytically determined by means of HPLC-MS/MS and published from 2011 to 2015. Only seven papers reported such values, four of which referred to population studies [ 18 , 19 , 20 , 21 ] and three to controls in studies on occupational exposures [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also examined other published data regarding urinary concentrations of SPMA in subjects without occupational exposure, all analytically determined by means of HPLC-MS/MS and published from 2011 to 2015. Only seven papers reported such values, four of which referred to population studies [ 18 , 19 , 20 , 21 ] and three to controls in studies on occupational exposures [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…One epidemiological study reported in 2013 found an elevated incidence of lung cancer in non-smoking Chinese women who cooked/fried food at very high temperatures using a traditional Chinese-style wok process, and hence had a high level of exposure to cooking oil fumes arising therefrom [130]. Supporting laboratory evidence for this hypothesis was provided by the observation that these women participants excreted significantly higher creatinine (Cn)-normalised concentrations of acrolein and crotonaldehyde (the latter the next higher trans-2-alkenal homologue from acrolein) as their mercapturate metabolites.…”
Section: Acrolein and Chinese Wok Cookingmentioning
confidence: 99%
“…According to the study carried out by Hecht et al [45], exposed to CFs has statistically significant effects on the levels of 3-hydroxy propylmercapturic acid and 3-hydroxy-1-methylpropylmercapturic acid, but not Sphenylmercapturic acid. The level of creatinine 3-hydroxypropylmercapturic acid of women cooking more 7 times a week was 36.8% higher than that of women who cooking less than once a week.…”
Section: Cooking Fumes Effects On the Blood Circulation Systemmentioning
confidence: 99%